The Rolling Stones 50 - Jagger, Mick 1943-; Richards, Keith 1943-; Watts, Charlie 1941-2021; Wood, Ronnie 1947- (Thames & Hudson, 2012)
This is our story of fifty fantastic years of the greatest rock 'n' roll band the world has ever known. Written by us, curated by us, and featuring the very best photographs and ephemera from and beyond our archives
Keywords: The Rolling Stones -- Musikgruppe; Geschichte 1962-2012; Pop & Rock; Biography & autobiography; Bildband; Biografie